Eating Behaviors of Early Childhood at a Selected Upazila in Bangladesh - Akter, Mariam; Gharami, Tumpa; Akter, Halima (Alta Dharma Publisher, 2025)
Background: Eating behavior plays a vital role in both the prevention and management of chronic illnesses associated with poor nutrition. Children who are overweight tend to display stronger food responsiveness, derive more enjoyment from eating, and often consume more food in response to emotional cues. The aim of this study was to assess eating behaviors among young children in a selected Upazila of Bangladesh. Methods: This cross-sectional study included a total of 103 mothers with children aged between 1 and 5 years. Participants were chosen using a convenience sampling method. Data were collected using a self-administered questionnaire comprising two sections: Part 1 included socio-demographic information, and Part 2 consisted of the Child Eating Behavior Questionnaire (CEBQ). Data analysis was performed using both descriptive and inferential statistics via SPSS version 26. Results: The study found a moderate overall mean score (2.91 ± 0.33) in children's eating behaviors, with variability observed across the eight subscales of the CEBQ. The average age of participating mothers was 27.75 years (SD = 3.816). Statistically significant associations were observed between children’s eating behaviors and various socio-demographic factors, including mothers’ education level (F = 5.519, p = 0.005), fathers’ education level (F = 7.328, p = 0.000), fathers’ occupation (F = 2.687, p = 0.036), and the number of siblings (r = 0.334, p = 0.001). Conclusion: The findings highlight meaningful associations between several demographic variables and children's eating behaviors. These results support the need for policy-level initiatives aimed at promoting food security and balanced nutrition during early childhood, with the goal of reducing malnutrition and supporting healthy development in Bangladesh.